2017
DOI: 10.1007/s10895-017-2179-y
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Combustion Synthesis of ZnO:Eu Nanoparticles: Effect of Fuel Types

Abstract: Nanoparticles of Europium oxide doped with Zinc oxide were synthesized via microwave-assisted combustion method. Citric acid as a simultaneous fuel and chelating agent and glycine as a fuel and mixture of these fuels were sleeted. X-Ray diffraction patterns (XRD) indicated the formation of ZnO structure with a few amount of EuO phase. Fourier transformation infra red (FTIR) spectra reveal the increase of ZnO bonds with glycine content of fuels mixture. Scanning electron microscope (SEM) images showed the conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In recent years, many researchers indicate that Eu 3+ ions can incorporate into the ZnO matrix under suitable conditions because they observe the efficient red emissions from Eu 3+ -doped ZnO [11]. Therefore, several preparation techniques have been used to synthesize the Eu-doped ZnO such as sol-gel [20], microwave-assisted combustion [21], solidstate reaction [22], magnetron sputtering [23], hydrothermal [19,24,25], chemical vapor deposition [26,27] and electrodeposition [28]. Particularly, the hydrothermal method is considered as an attractive preparation process of Eu-doped ZnO due to the simplicity, low cost, the possibility of mass production and the environmental friendliness.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many researchers indicate that Eu 3+ ions can incorporate into the ZnO matrix under suitable conditions because they observe the efficient red emissions from Eu 3+ -doped ZnO [11]. Therefore, several preparation techniques have been used to synthesize the Eu-doped ZnO such as sol-gel [20], microwave-assisted combustion [21], solidstate reaction [22], magnetron sputtering [23], hydrothermal [19,24,25], chemical vapor deposition [26,27] and electrodeposition [28]. Particularly, the hydrothermal method is considered as an attractive preparation process of Eu-doped ZnO due to the simplicity, low cost, the possibility of mass production and the environmental friendliness.…”
Section: Introductionmentioning
confidence: 99%
“…Microwave hybrid synthesis method of ZnO composites or ZnO hybrid structures, where the literature review results [ 887 , 888 , 889 , 890 , 891 , 892 , 893 , 894 , 895 , 896 , 897 , 898 , 899 , 900 , 901 , 902 , 903 , 904 , 905 , 906 , 907 , 908 , 909 , 910 , 911 , 912 , 913 , 914 , 915 , 916 , 917 , 918 , 919 , 920 , 921 , 922 , 923 , 924 , 925 , 926 , 927 ] are summarised in Table 14 .…”
Section: Microwave Hybrid Synthesis Of Znomentioning
confidence: 99%
“…The microwave hybrid synthesis enables obtaining: ZnO doped with the following ions: Al 3+ [ 890 ], Ba 2+ [ 893 ], Co 2+ [ 895 , 896 ], Cu 2+ [ 904 , 914 ], Cr 3+ [ 897 ], Eu 3+ [ 907 , 908 ], Ga 3+ [ 910 , 911 ], Mg 2+ [ 915 ] and Sm 3+ [ 919 ]; ZnO co-doped with the following ions: Ce 2+ -Cu 2+ [ 894 ] and Mn 2+ -Co 2+ [ 917 ], where M = Mn 2+ , Ni 2+ , Fe 3+ and Cu 2+ [ 914 ]; composite and hybrid materials: Ag-ZnO [ 887 , 888 , 889 ], Au-ZnO [ 887 ], Ag–ZnO–graphene [ 889 ], Al 3+ doped ZnO/Sn doped In 2 O 3 [ 891 ], Au/Fe 2 O 3 –ZnO [ 892 ], ZnO/BiOBr [ 898 ], Zn–ZnO [ 899 , 900 ], ZnO–ZrO 2 [ 901 ], ZnAl 2 O 4 /ZnO [ 902 , 903 ], Cu–ZnO–Al 2 O 3 [ 905 ], Cu–ZnO [ 906 ], Fe 2 O 3 /ZnO [ 909 ], In 2 O 3 –Ga 2 O 3 –ZnO [ …”
Section: Microwave Hybrid Synthesis Of Znomentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the morphology of the samples shifted from nanosphere to sponge-like when the fuel mixture composition changed from citric acid to glycine. 74 Khort et al group produced metallic cobalt nanoparticles by microwave-assisted combustion and investigated the effects of different types of fuels (urea, citric acid, glycine and hexamethylenetetramine) on the combustion process and solid product properties. When hexamethylenetetramine was used as a fuel, the results showed that metallic Co nanoparticles with a wide size distribution (∼5–40 nm) could be synthesized by one-step solution combustion under normal air atmosphere.…”
Section: Microwave-induced Combustion Synthesis Of Nanomaterialsmentioning
confidence: 99%